Family mediation in Asia: a special reference to the law and practice in Malaysia - Abdul Hak, Nora (International Islamic University Malaysia, 2007)
This article seeks to discuss in general the practice of family mediation in some selected Asian countries. For this purpose the practice in Singapore, China, Japan and Hong Kong is described. However the focus of the article is the law and practice of conciliation in Malaysia which are governed by the Law Reform (Marriage and Divorce) Act, 1976. Some issues pertaining to the position of the non-Muslims in Malaysia are also highlighted.